Estrutura floral das angiospermas usadas por Heliconius erato phyllis (Lepidoptera, Nymphalidae) no Rio Grande do Sul, Brasil - Corrêa,Claudine A. (2001)
A field survey of flowering plants used as food resource by the adults of Heliconius erato phyllis (Fabricius, 1775) was carried out in four sites located in Rio Grande do Sul state, Brazil. Samples were taken in preserved areas of the Atlantic Rain and Myrtaceae forests, an Eucalyptus plantation, and an urban park. Adult feeding frequencies on flowers were registered monthly from December 1996 to May 1997, on plants located on previously marked 200 m long transects. Flowers on which H. erato phyllis fed in the field were collected, drawn and morphometrically characterized. Feeding was registered on flowers of twenty-three species, of which seventeen are new records for H. erato in Brazil . The use of a given plant varied among localities, as a function of its corresponding abundance. The most visited flowers were those of Lantana camara L. and Stachytarpheta cayennensis (Rich.) Vahl, followed by Dahliapinnata Voss in the urban site. The data suggest the existence of size and shape convergence between the proboscis and the small, tubular flowers upon which H. eratophyllis feeds. They also indicate that H. eratophyllis adults have an opportunistic nectar feeding / pollen gathering habit, using several of those flowers available in a given time and locality that fit such a morphometrical pattern. Since plant species of both primitive and derived families are used, there is no indication that phylogenetic constraints play a major role in this association, nor that color of flowers, growth pattern or size of the plants are relevant in determining their use by H. erato phyllis.